2016
DOI: 10.1038/srep36584
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance transport of radioactive plume by nocturnal local winds

Abstract: Radioactive plumes can spread far and wide depending on wind conditions. The plumes often frequently reached the Tokyo metropolitan area, which is approximately 200 km away from the Fukushima Daiichi nuclear power plant, under spatially heterogeneous wind fields in March 2011. To reduce exposure to radioactive plumes, the behaviour of the plumes must be known. However, the transport mechanism of radioactive plumes is not fully understood. Using a regional climate model, we show that multiple diurnal cycle proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…As described in Methods, validation of the regional trade of foods and the transport model was reported elsewhere [6,12]. A unit of μSv month −1 was used since the dose might be subject to temporary change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in Methods, validation of the regional trade of foods and the transport model was reported elsewhere [6,12]. A unit of μSv month −1 was used since the dose might be subject to temporary change.…”
Section: Resultsmentioning
confidence: 99%
“…Details and the validity of the transport model were reported previously [12]. Two emission conditions were used: actual and maximum emission conditions.…”
Section: Methodsmentioning
confidence: 99%
“…GPV‐MSM presents the results of the mesoscale climate model, whose domain covers the islands of Japan and its near seas, and it is provided by JMA. In this study, applying GPV‐MSM data is based on the study by Yoshikane et al (). The GPV‐MSM data used in this study are provided by the GPV Data Archiving in Kitsuregawa laboratories, IIS, The University of Tokyo.…”
Section: Methodsmentioning
confidence: 99%
“…According to the previous studies, the formation process of the highly concentrated distribution of 137 Cs in the Kanto region from 20 March through 23 March, hereafter called the hot spot, was such that the radioactive plume was transported from the FDNPP to the south by a northerly wind, passed through the metropolitan area via a northeasterly wind, and was deposited by precipitation (Kinoshita et al, ; Morino et al, ; Srinivas et al, ; Terada et al, ). In addition, the more precise process was investigated by Yoshikane et al (). They found that the northeasterly wind was associated with a mesoscale low‐pressure system, and they concluded that the transportation of the radioactive materials was related to the diurnal regional climate cycle in this area (Yoshikane et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation